Writing regional identities in Medieval England : from the Gesta Herwardi to Richard Coer de Lyon - Dolmans, Emily, 1988- (Cambridge : D.S. Brewer, 2020)
An examination of how regional identities are reflected in texts from medieval England.
Introduction -- 1. Coping with Conquest: Local Identity and the Gesta Herwardi -- 2. The View from Lincolnshire: Gaimar's Estoire des Engleis as Regional History -- 3. Locating a Border: Fouke le Fitz Waryn and the March of Wales -- 4. Englishness Outside England: Embracing Alterity in Medieval Romance -- 5. England at the Edge of the World -- Envoi -- Bibliography -- Index.
Includes bibliographical references and index.
Online resource; title from PDF title page (ProQuest Ebook Central, viewed August 06, 2020).
JSTOR
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism; Regionalism in literature; Regionalism -- Great Britain -- History; Nationalism -- Great Britain -- History; Great Britain -- Civilization -- 1066-1485.; Littérature anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique; Littérature régionale.; Régionalisme -- Grande-Bretagne -- Histoire; Nationalisme -- Grande-Bretagne -- Histoire; Grande-Bretagne -- Civilisation -- 1066-1485.; Regionalism in literature; English literature -- Middle English; Civilization; Nationalism; Regionalism; Great Britain; 1066-1500; Cultural Influences; Gesta Herwardi; Identity Formation; Literature; Medieval England; Regional Identities; Richard Coer de Lyon; Writing; Electronic books; Literary criticism; Criticism, interpretation, etc; History; Literary criticism; Critiques littéraires.